Investigação geofísica da contaminação por derivados de hidrocarbonetos nas redondezas do Posto Cristal (Belém-Pa) - SILVA, Márcio Antonio dos Santos (2013)
This dissertation approaches a possible contamination in the surroundings of a gas station in Belém - Pa. It was made a reunion of the existing technical data as well as the investigation with the Grounding Penetration Radar (GPR) method, and the electric induced polarization (IP) and resistivity methods. The degree of difficulty that the problem represents for the geophysics is extreme, because the signature of the contamination confuses with the clay, abundant in the mantle of weathering that covers the region,be it because there is no description of borehole. Despite of this, at least one of the profile suggests the presence of contamination in the residual phase and others permit to guide the perforation for the confirmation of the results. The results show that the classification of the leakage in the class 3 of the ASTM E1739-95 as attributed before is improper, because the situation seems to be more serious